2011
DOI: 10.1002/14651858.cd004916.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to slow progression of myopia in children

Abstract: Istotność kontroli krótkowzroczności jest związana z rosnącym odsetkiem światowej populacji obarczonej tą wadą wzroku, a jest ona jednym z czynników ryzyka wystąpienia innych chorób oczu. W licznych pracach poddawano analizie wpływ różnych metod optycznych i farmakologicznych na spowolnienie progresji krótkowzroczności. Stosowano zarówno korekcję okularową i soczewkami kontaktowymi o konstrukcjach dwu-i wieloogniskowych, jak i ortokeratologię. Wśród leków badano przede wszystkim wpływ różnych stężeń atropiny n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
132
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 218 publications
(153 citation statements)
references
References 144 publications
2
132
0
2
Order By: Relevance
“…The 2 studies actually found less progression of refractive error in the full-power group by 0.15 D, 14,15 an effect that was significant when the results were pooled in a subsequent Cochrane review. 13 These studies did not randomize children to go without glasses altogether, report on VA, or include many Chinese children (41 participants [44%] in Chung and associates 15 ). Current sparse trial evidence is thus consistent in suggesting that correction of refractive error with glasses may be protective against, or is at least unlikely to worsen, declines in VA due to myopic progression with aging in children.…”
Section: Results From Itt Analysis In This Randomized Trialmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2 studies actually found less progression of refractive error in the full-power group by 0.15 D, 14,15 an effect that was significant when the results were pooled in a subsequent Cochrane review. 13 These studies did not randomize children to go without glasses altogether, report on VA, or include many Chinese children (41 participants [44%] in Chung and associates 15 ). Current sparse trial evidence is thus consistent in suggesting that correction of refractive error with glasses may be protective against, or is at least unlikely to worsen, declines in VA due to myopic progression with aging in children.…”
Section: Results From Itt Analysis In This Randomized Trialmentioning
confidence: 99%
“…It is this latter effect of glasses on the uncorrected vision that is not known. Previous small studies [13][14][15] have been inconclusive on the effect of glasses wear on refractive power, and have not compared wear of glasses with nonwear, or directly reported effects on VA.…”
mentioning
confidence: 99%
“…Two independent research groups, using genome-wide association studies, have identified 20 genetic loci that have been linked to myopia [7]. Environmental factors such as long periods of near work, type of optical correction, and limited outdoor time also affect myopia development [8][9][10][11]. One study reported that increasing time spent outdoors can delay the onset of myopia [12].…”
Section: Introductionmentioning
confidence: 99%
“…Substantial increases in axial length and the resulting myopic progression requires repeated refractive corrections during childhood, and places those with higher myopia at risk of sight-threatening complications such as maculopathy, retinal detachment, cataracts and glaucoma [13][14][15][16][17]. Once myopia develops, various methods of slowing its progression have been attempted in conjunction with clinical testing of these methods [11,[18][19][20]. These include pharmaceutical agents such as atropine, multifocal spectacle lenses, specially-designed soft contact lenses, rigid gas-permeable contact lenses, spectacle under-correction, and Orthokeratology (Ortho-K) [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation